Chemical Targeting of a G-Quadruplex RNA in the Ebola Virus L Gene. Issue 9 (22nd September 2016) - Wang, Shao-Ru; Zhang, Qiu-Yan; Wang, Jia-Qi; Ge, Xing-Yi; Song, Yan-Yan; Wang, Ya-Fen; Li, Xiao-Dan; Fu, Bo-Shi; Xu, Guo-Hua; Shu, Bo; Gong, Peng; Zhang, Bo; et al.
Summary: In the present study, our bioinformatics analysis first reveals the existence of a conserved guanine-rich sequence within the Zaire ebolavirus L gene. Using various methods, we show that this sequence tends to fold into G-quadruplex RNA. TMPyP4 treatment evidently inhibits L gene expression at the RNA level. Moreover, the mini-replicon assay demonstrates that TMPyP4 effectively inhibits the artificial Zaire ebolavirus mini-genome and is a more potent inhibitor than ribavirin. Although TMPyP4 treatment reduced the replication of the mutant mini-genome when G-quadruplex formation was abolished in the L gene, its inhibitory effect was significantly alleviated compared with wild-type. Our findings thus provide the first evidence that G-quadruplex RNA is present in a negative-sense RNA virus. Finally, G-quadruplex RNA stabilization may represent a new therapeutic strategy against Ebola virus disease. Graphical Abstract: Highlights: A conserved guanine-rich sequence is present in the Zaire ebolavirus L gene This sequence tends to fold into a G-quadruplex RNA structure TMPyP4 inhibits intracellular replication of artificial Zaire ebolavirus mini-genome G-quadruplex RNA stabilization represents a new strategy against Ebola virus disease Abstract : Wang et al. describe a small molecule that targets the G-quadruplex RNA structure in a negative-sense RNA virus. G-quadruplex RNA stabilization may represent a new therapeutic strategy against Ebola virus.